A simulation-based evaluation of a disk I/O subsystem for a massively parallel computer: JUMP-1 - Nakajo, H.; Ohtani, S.; Kaneda, Y. (Proceedings of the 16th International Conference on Distributed Computing Systems, 2002)
JUMP-1 is a distributed shared-memory massively parallel computer and is composed of multiple clusters of inter-connected network called RDT (Recursive Diagonal Torus). Each cluster in JUMP-1 consists of 4 element processors, secondary cache memories, and 2 MBP (Memory Based Processor) for high-speed synchronization and communication among clusters. The I/O subsystem is connected to a cluster via a high-speed serial link called STAFF-Link. The I/O buffer memory is mapped onto the JUMP-1 global shared-memory to permit each I/O access operation as memory access. In this paper we describe evaluation of the fundamental performance of the disk I/O subsystem using event-driven simulation, and estimated performance with a Video On Demand (VOD) application.